Characterization of brewery wastewater with spectrofluorometry analysis - Janhom T. (2014)
The wastewater treatment systems from the three local breweries consist of upflow anaerobic sludge blanket (UASB) and activated sludge (AS) connected in series for which the influent and effluent from each treatment step were collected and determined for their dissolved organic matter (DOM) surrogate parameters including dissolved organic carbon (DOC), UV254 and SUVA254. The analyses suggested that the influent wastewater contained a high level of aromatic organic content classified as humic substances with high average molecular weight. Organic removal mostly occurred in the UASBs where DOC and UV254 were reduced by 24-58% and 38-50%, respectively. Spectrofluorometry analysis (fluorescent excitation-emission matrix: FEEM) was reasonably accurate in evaluating DOM reduction during the treatment course. A total of eight fluorescent peaks were detected by the FEEM technique comprising (A) 230 nmEx/315 nmEm, (B) 275 nmEx/315 nmEm, (C) 230 nmEx/365 nmEm, (D) 285 nmEx/365 nmEm, (E) 290 nmEx/400 nmEm, (F) 335-355 nmEx/405-465 nmEm, (G) 255 nmEx/455 nmEm, and (H) 500 nmEx/525 nmEm. Peaks 'A and B' and 'C and D' were associated with tyrosine-like, tryptophan-like substances, respectively, whilst each individual peak E, F and G was associated with humic and fulvic acid-like substances. Peaks C, D, F and H were always found in the influent wastewater from all the breweries, whereas the effluents only exhibited Peak F. The origin of Peak H had not been recognized elsewhere and was not identified in this work. This suggested that FEEM could not only be used to monitor the reduction in DOM, but it could also provide details on the organic composition of the wastewater. © 2008 Elsevier Ltd. All rights reserved.